ANALISIS YURIDIS PENEGAKAN HUKUM LINGKUNGAN TERHADAP PENCEMARAN LAUT DI WILAYAH PESISIR PANTAI LAKESSI KOTA PAREPARE - ibrahim (FAKULTAS HUKUM UM PAREPARE, 2019)
This study is a study that aims to find out how the law enforcement arrangements against Sea pollution in the coastal areas of Lakessi and how the influence of public legal awareness in law enforcement against waste pollution in the coastal areas of Lakessi Coast of Parepare. In this study the authors used a type of normative-empirical research that the authors obtained from regional laws and interviews with the surrounding community. The writing of this journal also the author collects data in accordance with the type of research that the author obtained, namely by field studies and literature studies as for the data analysis technique that the authors use is qualitative descriptive analysis. The research results obtained by the author are that the government has not optimally used 3 legal instruments namely, Administrative Law Enforcement, Civil Law and Criminal Law. And in the process of enforcing coastal areas in Lakessi it is still very low, due to the absence of socialization, the lack of adequate bins / trash bins, hands off / lack of decisive action from the government related to sea pollution in the coastal areas